The importance of virtual environments in current education - Salazar Avelar, Brandon Ernesto
The Internet has brought new alternatives into our lives, one being virtual learning environments. These educational technologies have helped teachers diversify the teaching-learning environment since the COVID-19 pandemic affected traditional teaching methods. Thus, the world of teaching and learning implemented new options to develop classes and become more interactive. The objective of this report is to present how the course of Specialization in the Administration of Virtual Environments for Teaching Foreign Languages developed over six months in virtual mode and to describe the different activities carried out during this time, the activities performed in class as teachers to evaluate the students. During the sessions and evaluations, some tools taught and used, either those that are LMS (Learning Management System) or those that cannot be in that group: Nearpod, Edmodo, Schoology, Liveworksheet, and some other platforms, for example, Google site to have a better learning delivery. This report contains a brief description of them. Finally, this will provide what the students achieved by participating in this specialization course and some recommendations